Refleksi Atas Etika Lingkungan John Galtung - Heru Santosa (Jurnal Filsafat "WISDOM", 2004)
Environmental ethics theoritically is dreamed as a reading matter which may build a new understanding of modern enviroment probelms. This is the reason on what environmental ethics mus be developed beside in order to change view point to the better one, point of view that inculcates honor and friendship attitude to environment it self.